Advances in the structural composition of biomass: Fundamental and bioenergy applications - Srivastava N.; Shrivastav A.; Singh R.; Abohashrh M.; Srivastava K.R.; Irfan S.; Srivastava M.; Mishra P.K.; Gupta V.K.; Thakur V.K. (My University, 2025)
Increased environmental pollution due to the organic wastes over the world is one of the most burning issues. These organic wastes lie under the category of biodegradable waste and can be effectively degraded from their complex compound into simple one by the action of microbes or other living organisms. Moreover, lignocellulosic biomass is a major part of the biodegradable waste and belongs to the group of renewable energy source, which can be very effective for bioenergy production. Biomasses are made up of different compounds such as cellulose, hemicelluloses, lignin and protein. Apart from these components, based on the structural analysis biomass also consist of bioactive substances such as carotenoids, flavonoids, lignin and antioxidants. This review explores a complete overview of the classification, component and the structure of the biomass. Moreover, it discusses how biomasses can play the key role of substrate in many sectors such as industrial bioenergy production including gaseous and liquid biofuels. © 2021, Tech Science Press. All rights reserved.